Type 2 inhibitor leads of human tropomyosin receptor kinase (hTrkA). Issue 19 (1st October 2019) - Subramanian, Govindan; Bowen, Scott J.; Zhu, Yaqi; Roush, Nicole; Zachary, Theresa; Javens, Christopher; Williams, Tracey; Janssen, Ann; Gonzales, Andrea
Graphical abstract: Abstract: In silico virtual screening using the ligand-based ROCS approach and the commercially purchasable compound collection from the ZINC database resulted in the identification of distinctly different and novel acetamide core frameworks with series representatives 1a and 2a exhibiting nanomolar affinity in the kinase domain only h TrkA HTRF biochemical assay. Additional experimental validation using the Caliper technology with either the active or inactive kinase conditions demonstrated the leads, 1a and 2a, to preferentially bind the kinase inactive state. X-ray structural analysis of the kinase domain of h TrkA…1a /2a complexes confirmed the kinase, bind the inhibitor leads in the inactive state and to exhibit a type 2 binding mode with the DFG-out and αC-helix out conformation. The leads also demonstrated sub-micromolar activity in the full length h TrkA cell-based assay and selectivity against the closely related h TrkB isoform. However, the poor microsomal stability and permeability of the leads is suggestive of a multiparametric lead optimization effort requirement for further progression.